Enquête ethanobotanique des plantes médicinales de la pharmacopée traditionnelle dans le traitement des morsures de serpents (région du Souf) - ATALLAH, Sara; DIAB, Sara (University of Eloued جامعة الوادي, 2023)
This work aims at identifying a ethnobotanical study in El-Oued region (Algerian Sahara), which is characterized by rich and diverse medicinal plants. A series of surveys were conducted in the study area among the local population (100 questionnaires) in order to obtain as much information as possible on the therapeutic uses of medicinal plants. The results obtained by the residents allowed the identification of six types Soak and boiling are the two most commonly used methods to treat a number of conditions, particularly vivid poisoning especially digestive system diseases, infectious diseases, high blood pressure, neurological diseases, urology and tumors. Thus, this study is an important source of information that contributes to the knowledge of medicinal plants and how to use phytotherapy. This study can serve as a database for evaluating this precious resource with a view to finding new active ingredients that can be used in pharmacology.
Biodiversité et Physiologie Végétale
Keywords: Scanning; snake bites; medicinal plants; traditional herbal medicine; Oued Souf.; النباتات الطبية ، الطب التقليدي ، لدغات الأفاعي